Antinociceptive and anti-inflammatory properties of Corchorus capsularis leaves chloroform extract in experimental animal models - Zakaria, Zainul Amiruddin; Sulaiman, Mohd Roslan; Gopalan, Hanan Kumar; Abdul Ghani, Zuleen Delina Fasya; Raden Mohd Nor, Raden Nur Suraya; Mat Jais, Abdul Manan; Abdullah, Fatimah Corazon (The Pharmaceutical Society of Japan, 2007)
The antinociceptive and anti-inflammatory properties of Corchorus capsularis leaves chloroform extract were investigated in experimental animal models. The antinociceptive activity was measured using the writhing, hot plate and formalin tests, while the anti-inflammatory activity was measured using the carrageenan-induced paw edema test. The extract, obtained after 72 h soaking of the air-dried leaves in chloroform followed by in vacuo evaporation to dryness, was weighed and prepared by serial dilution in DMSO in the doses of 20, 100 and 200 mg/kg. The extract was administered (s.c.) 30 min prior to subjection to the respective assays. The extract was found to exhibit significant (p<0.05) antinociceptive and anti-inflammatory activities. As a conclusion, the present study confirmed the traditional claims of using C. capsularis to treat various ailments related to inflammation and pain.